Fake Profiles Types of Online Social Networks: A Survey - Kareem, Rafeef; Bhaya, Wesam (International Journal of Engineering and Technology, 2018)
Today, OSNs (Online Social Networks) considered the most platforms common on the Internet. It plays a substantial role for users of the internet to hold out their everyday actions such as news reading, content sharing, product reviews, messages posting, and events discussing etc. Unfortunately, on the OSNs some new attacks have been recognized. Different types of spammers are existing in these OSNs. These cyber-criminals containing online fraudsters, sexual predators, catfishes, social bots, and advertising campaigners etc.OSNs abuse in different ways especially by creating fake profiles to carry out scams and spread their content. The identities of all these malicious are so damaging to the service providers and the users. From the opinion of OSNs service providers, the loss of bandwidth moreover the overall reputation of the network is affected by fake profiles. Thus, needing more complex automated methods, and tremendous effort manpower to discover and stopping these harmful users.This paper explains different kinds of OSNs risk generators such as cloned profiles, compromised profiles, and online bots (spam-bots, chat-bots, and social-bots). In addition, it presents several classifications of features that have been used for training classifiers in order to discover fake profiles. We try to show different ways that used to detect every kind of these malicious profiles. Also, this paper trying to show what is the dangerous type of profile attacks and the most popular in OSNs.Â Â